Wag-Based E-Book Development in English Class VII Students SMPN 1 Songgon Banyuwangi - Tri Tijantini; Rufii; Djoko Adi Walujo (Jurnal Mantik, 2022)
The purpose of this development is to produce a WAG-Based E-Book learning media in the form of an electronic book with English subject matter. The development model used in the development of interactive learning multimedia is the Borg & Gall model. The research and development stages of the Borg & Gall model consist of ten steps. The development process involves subject matter experts, instructional design experts and learning media experts to provide feedback and suggestions for improvement. In addition, the English teacher and class VII students of SMPN 1 Songgon Banyuwangi as users of this WAG-Based E-Book also gave their feedback and input. The results of this development research are (1) the product development in the form of an E-Book based on WAG learning English for Class VII Students of SMPN 1 Songgon Banyuwangi has been improved based on the analysis of trial data. Aspects revealed to carry out revisions include: content experts, design experts, media experts, individual trials, small group trials, field trials, and peer trials, (2) There are several things that need to be improved in product development. According to content experts, the level of difficulty in making questions needs to pay attention to students' abilities, and (3) As for the peer test, giving advice on writing a bibliography must be in accordance with the level of writing a bibliography. Individual tests and field tests on average gave the respondents a choice of answers, very good/very appropriate and good/appropriate. Also giving a positive impression in the development of WAG-Based E-Book products themselves, they prefer WAG-Based E-Books as teaching materials that can add information according to their respective expertise competencies and can also increase independent learning for students.